Gut Microbiota and Alzheimer Disease - Lester Raymundo Dominguez Huarcaya (Acta Neurologica Taiwanica)
The hallmarks of Alzheimer’s disease (AD) include brain dysfunction and the buildup of amyloid and tau proteins. The onset of dementia is one of the latter symptoms. Imaging diagnostics allowed for the detection of amyloid buildup in the brain 10–20 years before the emergence of overt signs of the disease. The application of imaging diagnostic techniques allowed for this identification. Within the next few decades, the incidence and frequency of this disease are expected to reach epidemic proportions unless measures are done to stop or slow its growth. However, unless action is taken to slow or stop the disease’s progression, it will continue to threaten the health of the general public. Recently, there has been some speculation that the gut flora might contribute to the development of AD. Not only that, but the rapidly expanding ischemia etiology is another possible contributor to the issue. Rumor has it that there’s a network connecting the brain and the stomach called the “gut-brain-microbiota axis.” The hypothesis is based on this network. Furthermore, a large amount of evidence implies that the gut microbiota (GMB) could potentially contribute to the onset of AD. It has been suggested that the GMB could play a role in the onset of AD. This notion has been bolstered by new studies. It is quite probable that this review will address the prospect of a link between the microbiome and AD. This concept could be explored as a potential therapy or preventative measure. Some techniques that show promise as new treatments for AD include changes to the GMB, which can be achieved through dietary changes or positive microflora interventions, and changes to microbiological partners and their products, like amyloid protein.